2016
DOI: 10.1155/2016/2968410
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and Digital Morphometrical Evaluation of Uterine Leiomyoma in Brazilian Women

Abstract: The current study aims to evaluate histopathological and digital morphometrical aspects associated with uterine leiomyomas in one hundred and fifty (150) patients diagnosed with leiomyoma. Uterine tissues were subjected to the histopathological and digital morphometric analyses of the interstitial collagen distribution. The analysis of medical records indicates that most of the women diagnosed with uterine leiomyomas (68.7%) are between 37 and 48 years old. As for the anatomic location of the tumors, approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…1 These are the most common benign tumors of uterus affecting 20-40% women of reproductive age group. [2][3][4] The diagnosis is easily established by complete history and radiological findings. The histopathological examination analyses are the important tool to qualify and quantify the tumor according to the histopathological parameters that enable differential diagnosis of the neoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…1 These are the most common benign tumors of uterus affecting 20-40% women of reproductive age group. [2][3][4] The diagnosis is easily established by complete history and radiological findings. The histopathological examination analyses are the important tool to qualify and quantify the tumor according to the histopathological parameters that enable differential diagnosis of the neoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Flake and colleagues categorized uterine leiomyoma in 4 different phases on the basis of percent collagen content ranging from none (phase 1) up to 72% (>50%, phase 4) independently of the tumor size 67 . The collagen content in myometrium ranged from 0.3% to 23% in our previous samples 11 and from 1.6% up to 20.70% in Da Silva’s study 66 . Interestingly, the leiomyoma tissues appeared inhomogeneous also in stiffness, quantified through rheometry by measuring complex shear moduli of the tissues.…”
Section: Discussionmentioning
confidence: 46%
“…We and others have recently observed that the amount of collagen inside tissues within and between biopsies is heterogeneous mainly in leiomyoma, but also in myometrial tissue. For example, morphometric analysis of Masson’s trichrome stained tissue reported values of collagen in leiomyoma ranging from 4.7% to 31,3% in our previous study 11 ; from 37% to 77% in Jayes 65 study and from 3.9% up to 70% in a large study of brazilian cases (n = 150) performed by Da Silva 66 . Flake and colleagues categorized uterine leiomyoma in 4 different phases on the basis of percent collagen content ranging from none (phase 1) up to 72% (>50%, phase 4) independently of the tumor size 67 .…”
Section: Discussionmentioning
confidence: 70%
“…Миома матки -одна из наиболее распространенных доброкачественных опухолей малого таза у женщин. Она выявляется у 20-40 % пациенток репродуктивного возраста [51]. Миома матки больших размеров, которая сдавливает окружающие ткани, нарушая циркуляцию крови в венах малого таза, также может стать причиной ТЭЛА [52,53].…”
Section: ключевые словаunclassified